Characterization of physical, structural and antioxidant properties of hemp seed and seed meal protein-gallic acid conjugates - Wannawarang Tanbamrung; Suphat Phongthai; Pornchai rachtanapun; Kongsak Boonyapranai; Prem Thongchai; Liang Zhang; Kanyasiri Rakariyatham (Applied Food Research)
This study investigated the effects of covalent modification of hemp protein isolates (HPIs) from seed and seed meal under alkaline reaction with gallic acid (GA) on physical, structural and antioxidant properties. By increasing the amount of GA (0 – 1000 μmol) during the conjugation process to form HPI-GA conjugates (HPI-GA0–1000), the binding between HPIs and GA were increased as total phenolic content of seed HPI-GA (sHPI-GA) conjugate significantly increased from 1.43 – 21.43 μg GAE/mg sample, although the binding efficacy of seed meal HPI-GA (smHPI-GA) conjugate was not as high. Simultaneously, there was a decrease in free thiol groups and tryptophan residues to be as low as 2.05 and 2.14 %, respectively in sHPI-GA1000 and 10.34 and 17.30 %, respectively in smHPI-GA1000 with an increase in molecular masses, indicating covalent bonding between HPIs and GA. Ultraviolet-visible and Fourier transform infrared spectroscopy revealed changes in the conjugate structures. Scanning electron microscopy also displayed roughness on the particle's surface. Increased zeta potential of HPI-GA conjugates from 31.80 to 51.12 mV in seed and from 24.65 to 33.83 mV in seed meal partially led to improved solubility at neutral and basic pHs. This subsequently improved antioxidant capacities by increasing DPPH radical scavenging (1.94 – 4.65-fold) and ABTS radical scavenging (8.65 – 9.64-fold) to be as high as 421.69 and 2560.26 μg TE/mg protein, respectively in sHPI-GA1000 and 719.31 and 2332.39 μg TE/mg protein, respectively in smHPI-GA1000. These results provide useful information on plant protein-phenolic conjugates for the design of functional protein-based ingredients.